Determinants of Household Energy Choices in Somalia: Applied Multinomial Logistic Regression Model - Ali, Dahir Abdi; Mohamud, Mohamed Ali; Tuyiragize, Richard (International Journal of Energy Economics and Policy, 2025)
This paper aims to examine the predictors that influence household energy choices for lighting and cooking in Somalia. Energy is one of the essential commodities that are strongly tied to household’s quality-of-life. The paper uses a multinomial logistic regression model to analyze data from the Somalia Integrated Household Budget Survey (SIHBS) 2022. The findings indicate that electricity and torches are the most common energy sources for lighting while charcoal and firewood are the predominant cooking energy sources. In Somalia, household’s choice of energy for lighting and cooking is influenced by the household head’s age, level of education, gender, geographical location, access to electricity, housing quality and per capita consumption. From the findings, it is recommended that policymakers should address the underlying barriers that prevent households from adopting sustainable energy solutions that result in improved health outcomes, environmental sustainability and economic development.